Internalization of Pancasila Economics Values in Elementary School Students - Sri Umi Mintarti Widjaja (Faculty of Economics, State University of Jakarta., 2021)
This study aims to find out how to be wise in instilling Pancasila-based economic values ​​in elementary school students and implementing their economic learning. The qualitative descriptive method is used in this research. The research participants were teachers at SD Negeri Kampungdalem I, SD Negeri Bungur I, and SD Negeri Ngentrong, who teach in grades 1-5. Data collection was carried out by observation, documentation, and in-depth interviews. Furthermore, data analysis reduces data, displays or displays data, and finally. The data triangulation method was used to test the validity of the data before dis. The results of the study as a whole show that elementary school teachers make efforts in applying the economic value of Pancasila to students. These efforts have a positive impact in shaping students' character based on the economic values ​​of Pancasila. Even so, the application of Pancasila economic values ​​for early childhood in elementary schools needs improvement. Schools also provide more support and attention to these efforts.